Zgodnje odkrivanje maligne alteracije pigmentnih znamenj - Golmajer, Peter (Medicinski razgledi, 1997)
Malignant melanoma is a highly malignant tumor, and its response to treatment is poor. Its incidence is on an increase world-wide. Amplified surface microscopy is a riew non-invasive diagnostic method enabling the detection of atypical (dysplastic) nevi, which are frequent precursors of malignant melanoma, as well as of signs that indicate the initial symptoms of malignant afteration much earlier than it used to be possible by a standard clinical examination. Therefore, our study was aimed at establishing the reliability and accuracy of amplified surface microscopy in comparison with standard dinical examination. The investigated group consisted of 41 individuals eithermeeting the criteria for clinical diagnosis of atypical nevus or malignant melanoma, or presenting with at least one cleary exoressed indicatorfor atypical nevus. The suspidous nevi were afterwards also examined by amplified surface microscopy and the results compared to the histological findings. It has been found that amplified surface microscopy is better and more reliable than clinical examination. This finding has been statistically confirmed; the degree of risk was less than 1 %.
Keywords: Dysplastic nevus syndrome; kožni rak; Diagnosis; Pathology; Melanoma; Skin neoplasms; Nevus, pigmented; Biopsy; Microscopy; melanom; diagnostika